5-azacitidine in aggressive myelodysplastic syndromes regulates chromatin structure at PU.1 gene and cell differentiation capacity - Čuřík, Nikola; Burda, Pavel; Vargová, Karina; Pospíšil, Vít; Beličková, Monika; Vlčková, Petra; Savvulidi, Filipp; Nečas, Emanuel; Hájková, Hana; Haškovec, Cedrik; Čermák, Jaroslav; Krivjanska, Maria; et al. (Leukemia, 2012)
Epigenetic 5-azacitidine (AZA) therapy of high-risk myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) represents a promising, albeit not fully understood, approach. Hematopoietic transcription factor PU.1 is dynamically regulated by upstream regulatory element (URE), whose deletion causes downregulation of PU.1 leading to AML in mouse. In this study a significant group of the high-risk MDS patients, as well as MDS cell lines, displayed downregulation of PU.1 expression within CD34+ cells, which was associated with DNA methylation of the URE. AZA treatment in vitro significantly demethylated URE, leading to upregulation of PU.1 followed by derepression of its transcriptional targets and onset of myeloid differentiation. Addition of colony-stimulating factors (CSFs; granulocyte-CSF, granulocyte-macrophage-CSF and macrophage-CSF) modulated AZA-mediated effects on reprogramming of histone modifications at the URE and cell differentiation outcome. Our data collectively support the importance of modifying the URE chromatin structure as a regulatory mechanism of AZA-mediated activation of PU.1 and induction of the myeloid program in MDS.
Keywords: buněčná diferenciace; azacytidin; Regulatory Sequences, Nucleic Acid; Humans; regulační oblasti nukleových kyselin; Antimetabolites, Antineoplastic; lidé středního věku; Female; Aged; faktory stimulující kolonie; senioři; chromatin; lidé; nádorové kmenové buňky; Neoplastic Stem Cells; myelodysplastické syndromy; protoonkogenní proteiny; Chromatin; Transcriptional Activation; Trans-Activators; aktivace transkripce; DNA Methylation; metylace DNA; ženské pohlaví; Male; Middle Aged; trans-aktivátory; regulace genové exprese u leukemie; Cell Differentiation; protinádorové antimetabolity; Aged, 80 and over; Proto-Oncogene Proteins; nádorové buněčné linie; Azacitidine; senioři nad 80 let; Colony-Stimulating Factors; Myelodysplastic Syndromes; Cell Line, Tumor; mužské pohlaví; Gene Expression Regulation, Leukemic